Historical Blue Pigments Used in India’s Wall Paintings-A Review - Sharma, Anjali; Rajdeo Singh, Manager (Cultural Arts Research and Development, 2024)
This review highlights the complexity of understanding historical blue pigments, focusing on their characterization, sources, and application in wall paintings. It discusses the Ajanta wall paintings, noting that past and current investigations have only scratched the surface. The dissemination of ideas along ancient trade routes influenced the sharing of painting materials and techniques, but each wall painting remains unique. A 13-year survey of Cappadocia’s rockcut churches illustrates continuity and diversity in Byzantine painting techniques. The use of mineral blue pigments in the Indian context is reviewed based on both analysis and literary sources. The article emphasizes the need for further research on pigment identification and durability in various types of paintings across regions and periods.